The Use of Fibre Bragg Grating To Monitor the Early Age Curing Temperature of Cement Paste - L. DONG; Z. IBRAHIM; Z. ISMAIL (Electronic Journal of Structural Engineering, 2013)
In this paper, a Fibre Bragg Grating (FBG) is used to monitor the early age curing temperature of cement paste. The FBG is inscribed by a Continuous Wave (CW) 244nm argon ion laser in the photosensitive fibre. The fabricated FBG is calibrated from room temperature to 105ºC. In this temperature range, the FBG is found to be in good conditions in both the sensitivity and linearity, which are around 9pm/ºC and 99.9%, respectively. In the experiment, the GP Portland cement, sand and water were mixed by volume of 800, 500, and 275 ml, respectively, as the host specimen. The results of the experiment prove that the FBG can determine the setting time of the specimen at the curing time of 5h.